Seed bank dynamics in tall-tussock grasslands along an altitudinal gradient - Funes, Guillermo (2003)
We studied the germinable soil seed bank of tall-tussock grasslands along an altitudinal gradient in the mountains of central Argentina. We selected 10 sampling plots at three altitudinal levels (1200 m, 1600 m and 2200 m). We assessed the composition of the established vegetation and took ten compound soil samples (0-5 cm depth) at each plot in autumn and spring. The soil samples were sieved, chilled, and incubated in a glasshouse to assess the composition of the seed bank. The similarity between the composition of the seed bank flora and that of the established vegetation was low throughout the gradient. Most species did not change their seed bank strategy along the gradient. Seed bank richness and density increased with altitude. Most species had a persistent seed bank at all altitudinal levels, and the proportion of such species increased with altitude. These results suggest that a cold climate directly and/or indirectly favours the formation of seed banks and seed persistence in the soil.